2022
DOI: 10.1101/2022.12.07.22283201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mpox knowledge, attitudes, beliefs, and intended behaviour in the general population and men who are gay, bisexual, and who have sex with men

Abstract: Objectives: To investigate rates of mpox beliefs, knowledge, and intended behaviours in the general population and in gay, bisexual or other men who have sex with men (GBMSM), and factors associated with intended behaviours. To test the impact of motivational messages (vs a factual control) on intended behaviours. Design: Cross-sectional online survey including a nested randomised controlled trial. Setting: Data collected 5 September to 6 October 2022. Participants: Participants were aged 18 years and over and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
2
15
1
Order By: Relevance
“…The study observed a significant positive association between mpox knowledge and the intention to self‐isolate as well as the intention to inform close contacts, consistent with a UK study linking knowledge of mpox‐related symptoms and transmission to the intention to self‐isolate 16 . Previous research, following the Knowledge‐Attitude‐Practice model, indicates that optimal health knowledge contributes to health promotion and disease prevention 36 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The study observed a significant positive association between mpox knowledge and the intention to self‐isolate as well as the intention to inform close contacts, consistent with a UK study linking knowledge of mpox‐related symptoms and transmission to the intention to self‐isolate 16 . Previous research, following the Knowledge‐Attitude‐Practice model, indicates that optimal health knowledge contributes to health promotion and disease prevention 36 .…”
Section: Discussionsupporting
confidence: 86%
“…The study illustrated that most participants intended to isolate themselves and inform close contacts after developing mpox‐related symptoms. The self‐isolation intention prevalence was higher than a previous UK study, 16 which reported 78.5% of gay and bisexual MSM (mean age: 47.1 years) would probably or definitely self‐isolate if they had mpox. Age could be a reason for the difference, as younger MSM may perceive higher mpox infection risk due to sexual activeness 27 and have a better understanding of the importance of both measures to halt transmission, which strengthens their intention to adopt preventive measures 34 .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…23 However, since the spring of 2022, mpox has garnered global attention, initiating an international outbreak impacting over 40,000 people in more than 80 countries. 24 The emergence of viral infections through the exotic pet trade is an unexpected threat, notably demonstrated in the 2003 human mpox outbreak in the United States, emphasising the risk posed by strange imported animals introducing new pathogens. 25 The zoonotic mpox virus, which causes a rare viral infection, bears resemblance to smallpox but typically presents with milder symptoms and a lower mortality rate.…”
Section: Mpox Epidemic Diseasementioning
confidence: 99%
“…It is marked by intermittent outbreaks and occasional small exported outbreaks in Western countries, including the US in 2003, the UK in 2018, and Israel in 2018 23 . However, since the spring of 2022, mpox has garnered global attention, initiating an international outbreak impacting over 40,000 people in more than 80 countries 24 …”
Section: Introductionmentioning
confidence: 99%